Rhythmicity in motor coordination in times of the COVID 19 pandemic - Eyzaguirre-Maldonado, Edwin Héctor (2022)
Rhythmicity is an important factor for the development of motor coordination, which allows movements to be carried out with an adequate duration, frequency and saving effort on the body. The study aimed to argue and support the importance of rhythmic capacity in motor coordination in the context of the COVID-19 pandemic. The applied methodology was the use of the information analysis technique on a topic; To do this, a review of articles and publications in indexed journals was carried out on the unit of analysis that is rhythmicity. The relevant conclusions are: Rhythmic performance is important in the person because it allows social integration, as well as influences physical, psychological and emotional factors. An adequate development or body availability is based on the rhythmic regulation that manifests itself in positive behaviors in various situations of daily life. Dance, as a rhythmic activity, generates mental processes of attention and concentration that help to consolidate a balanced corporal and emotional expressiveness. The rhythm, as a coordinative capacity, has a significant influence on the other capacities as a fundamental scaffolding for a regulation of motor coordination in general. Biological circadian rhythms are an indicator of the rhythmic presence within our body that enables rhythmic neuromotor regulation. The systematized rhythmic activity is a strategy that promotes a competent and suitable action in the person. Your practice must include a combination of rhythm-cognition-socialization that is expressed in dance and dances.